KEPEMIMPINAN RASULULLAH DALAM PERANG BADAR MENURUT PERSPEKTIF TEORI KEPEMIMPINAN OHIO - Alwi, Khanabi (Historia Islamica: Journal of Islamic History and Civilization, 2024)
Prophet Muhammad’s leadership in the Battle of Badr is a prime example of effective and successful leadership. The victory of the Islamic community in the Battle of Badr can be attributed to Prophet Muhammad’s high leadership in both the structural and human relations dimensions of Ohio leadership. The structural dimension pertains to how a leader organizes and directs tasks, while the human relations dimension involves how a leader builds relationships and interacts with followers. In the structural dimension, Prophet Muhammad demonstrated high leadership by crafting well-thought-out and precise war strategies, assigning tasks and responsibilities to the Islamic forces, and ensuring their readiness for battle. In the human relations dimension, Prophet Muhammad exhibited high leadership by providing motivation and spirit to the Islamic forces, attending to their needs and well-being, and fostering a harmonious relationship with them. His leadership in the Battle of Badr serves as a model for Muslims in leading various organizations and groups. With effective leadership, the Muslim community can achieve victory and success in diverse fields.